Exploring The Relationship between Personal Factors and Digital Competency Using The DigComp Framework among Vocational College Students - Mohamad, Marlina; Sugiman, Sukasih; Omar, Abdul Jalil; Mohamad, Asiah (Online Journal for TVET Practitioners, 2025)
The rapid expansion of digital technologies has transformed the skills demanded by modern economies, prompting educational institutions to adapt accordingly. Within Malaysia’s Technical and Vocational Education and Training (TVET) system, digital competencies are now emphasized as essential components of employability and lifelong learning. This study investigates the relationship between personal factors and digital competency levels among students in a Vocational College in Johor, guided by the European Commission’s DigComp Framework. A quantitative survey was conducted among 182 students across diploma and certificate programs. The instrument, adapted from the DigComp Self-Assessment Tool (DigCompSAT), assessed five key digital dimensions: information and data literacy, communication and collaboration, digital content creation, safety, and problem solving. Correlational analysis revealed a statistically significant positive relationship between personal factors, namely, access to ICT resources and participation in ICT-related training, and students’ digital competence levels. The findings suggest that individual exposure to digital environments outside formal education contributes meaningfully to students’ readiness for digitally mediated work contexts. The study highlights the need for enhanced access to digital infrastructure and targeted skills training as part of institutional strategies to strengthen digital readiness among vocational learners. These findings carry important implications for curriculum developers, TVET policymakers, and institutional leadership, who are responsible for ensuring that graduate competencies remain responsive to the dynamic requirements of the digital economy. Specifically, the integration of structured digital skills training, equitable access to digital infrastructure, and alignment of learning outcomes with the Malaysian Qualification Framework for digital competency should be prioritized to better prepare students for the realities of a technology-driven workforce.